Leveraging mobile-assisted language learning technology to boost english listening skills for students at SMK Walisongo Jakarta - Karimah, Syahadah Albaqiyatul; Zulianingrum, Ana; Zulha, Hani Fatimah; Muhjaj, Juniya Bintang; Muzhaffar, Djibriel Nabiel (Community Empowerment, 2025)
This community service program was conducted at SMK Walisongo Jakarta with the goal of improving students' English listening skills through a mobile-assisted language learning (MALL) approach. The program was designed based on a needs analysis that identified key challenges in mastering listening skills among vocational students. The initiative contributed to students' professional development by enhancing their English listening proficiency, a skill crucial for effective communication in various professional settings. Furthermore, it introduced them to mobile-assisted learning, thereby helping them develop independent study habits using accessible technology. The program’s implementation included a pre-test, an introduction to the MALL concept, demonstrations of supporting applications, structured listening practice sessions, and a final post-test. The evaluation results showed a substantial improvement in students’ listening abilities, with the average score rising significantly from 66.56 on the pre-test to 95.78 on the post-test. This indicates that through a structured approach and the use of accessible mobile technology, the program successfully achieved its goal of improving English listening skills and preparing students for workplace communication challenges. In conclusion, integrating MALL can be an effective method for English language learning that aligns well with the demands of the global industry.